Roze Drempel Nieuwsbrief - RD-Nieuwsbrief. - De Roze Drempel (RD) (Leuven : De Roze Drempel, 1987)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : p/a Amerikalaan 3, 3000 Leuven ; vanaf (1994) 12 : PB 113, 3000 Leuven
Vanaf 03(1989) 1 : RD-Nieuwsbrief
Nederlands
Periodiek